Naturally acquired immunity to sexual stage P. falciparum parasites. Issue 2 (8th January 2016) - STONE, WILL J. R.; DANTZLER, KATHLEEN W.; NILSSON, SANDRA K.; DRAKELEY, CHRIS J.; MARTI, MATTHIAS; BOUSEMA, TEUN; RIJPMA, SANNA R.
SUMMARY: Gametocytes are the specialized form of Plasmodium parasites that are responsible for human-to-mosquito transmission of malaria. Transmission of gametocytes is highly effective, but represents a biomass bottleneck for the parasite that has stimulated interest in strategies targeting the transmission stages separately from those responsible for clinical disease. Studying targets of naturally acquired immunity against transmission-stage parasites may reveal opportunities for novel transmission reducing interventions, particularly the development of a transmission blocking vaccine (TBV). In this review, we summarize the current knowledge on immunity against the transmission stages of Plasmodium . This includes immune responses against epitopes on the gametocyte-infected erythrocyte surface during gametocyte development, as well as epitopes present upon gametocyte activation in the mosquito midgut. We present an analysis of historical data on transmission reducing immunity (TRI), as analysed in mosquito feeding assays, and its correlation with natural recognition of sexual stage specific proteins Pfs48/45 and Pfs230. Although high antibody titres towards either one of these proteins is associated with TRI, the presence of additional, novel targets is anticipated. In conclusion, the identification of novel gametocyte-specific targets of naturally acquired immunity against different gametocyte stages could aid in the development of potential TBV targets and ultimately an effective transmission blocking approach.